Tác động của chất lượng thông tin báo cáo tài chính đến tính thanh khoản chứng khoán của các công ty niêm yết trên thị trường chứng khoán Việt Nam - Phạm Ngọc, Toàn; Dương Thị, Nhàn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
This paper attempts to address the reporting quality–stock liquidity relationship, using regression models to measure the impact of information quality of financial statements on the stock liquidity of 149 companies listed on HOSE and HNX in 2014. Furthermore, to measure stock liquidity, the study employs price and trading volume of the enterprises listed in early-2014 and at the end of first, second, third, and fourth quarters of the same year. Several characteristics of financial reporting quality include: (i) relevance, (ii) faithfulness; (iii), understandability; (iv) comparability; (v) timeliness; and (vi) verifiability, suggested to positively impact on the stock liquidity, which, in turn, is most significantly influenced by faithful representation. Based on the findings, a few recommendations are proposed to enhance liquidity of these enterprises.
Keywords: Information quality; financial statements; stock liquidity